Design of microcrystalline cellulose-free alginate spheroids by extrusion- spheronization technique / Siti Noorafifah Mohd Zolkefpeli - Mohd Zolkefpeli, Siti Noorafifah (2015)
Conventional spheroid preparation by extrusion-spheronization technique requires microcrystalline cellulose (MCC) as processing aid to improve extrudability of wet mass and spheronization capacity of extrudates. The present study investigated formulation and processing attributes in extrusion and spheronization necessary for design of MCC-free alginate spheroids. The physicochemical characteristics of these spheroids were examined and compared against MCC-Ioaded alginate spheroids using chlorpheniramine maleate and tolbutamide as water-soluble and poorly water-soluble drugs respectively. Alginate spheroids demonstrated a slower release of hydrophilic drug due to ease of matrix swelling and aggregation in the absence of MCC. This reduced their specific surface area for drug dissolution. Crosslinking of alginate with soluble calcium densified the surface of spheroids and hindered matrix aggregation. It led to faster drug release from alginate than alginate-MCC spheroids. Fast drug release was also noted in spheroids embedded with hydrophobic drug when MCC was absent as drug adsorbent. A complete replacement ofMCC with alginate can promote or retard drug release of spheroids as a function of drug-polymer interaction and state of matrix swelling and aggregation